The Reality of Using the Hologram in Teaching by Faculty Members - Rahman Shatat, Khalida Abdul (Opción, 2019)
This study aimed at finding out the reality of using the technology of hologram in teaching by faculty members and the factors that contribute to shaping this reality via a descriptive-analytical methodology. The results showed that hologram was not actually used in teaching, despite the desire and enthusiasm of faculty members to use it. In conclusion, in educational technology, the idea of hologram technology comes with a virtual reality design about the extent to which the learner can enter a realistic world created by default.